Property and prejudice: How racial attitudes and social‐evaluative concerns shape property appraisals. (21st May 2015) - McIntyre, Jason C.; Constable, Merryn D.; Barlow, Fiona Kate
Abstract: Property evaluations rarely occur in the absence of social context. However, no research has investigated how intergroup processes related to prejudice extend to concepts of property. In the present research, we propose that factors such as group status, prejudice and pressure to mask prejudiced attitudes affect how people value the property of racial ingroup and outgroup members. In Study 1, White American and Asian American participants were asked to appraise a hand‐painted mug that was ostensibly created by either a White or an Asian person. Asian participants demonstrated an ingroup bias. White participants showed an outgroup bias, but this effect was qualified. Specifically, among White participants, higher racism towards Asian Americans predicted higher valuations of mugs created by Asian people. Study 2 revealed that White Americans' prejudice towards Asian Americans predicted higher valuations of the mug created by an Asian person only when participants were highly concerned about conveying a non‐prejudiced personal image. Our results suggest that, ironically, prejudiced majority group members evaluate the property of minority group members whom they dislike more favourably. The current findings provide a foundation for melding intergroup relations research with research on property and ownership.